2018
DOI: 10.1002/macp.201800182
|View full text |Cite
|
Sign up to set email alerts
|

An Acid Test: Facile SI‐ARGET‐ATRP of Methacrylic Acid

Abstract: Atom transfer radical polymerization (ATRP) of methacrylic acid (MAA) is challenging. Herein is reported a study of conditions for facile surface‐initiated ATRP by activator regenerated electron transfer (SI‐ARGET‐ATRP) growth of poly‐methacrylic acid (PMAA) chains from a plasma polymer surface bearing surface‐immobilized α‐bromoisobutyryl bromide, with no deoxygenation required. Factors that affect PMAA polymer growth off the surface under ARGET‐ATRP conditions are systematically investigated, such as monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Previous reports for the thickness of EtOHpp under the same conditions ranged from 30–40 nm [ 33 ], which is within the range what has been achieved in this work. The same applies for the HMDSOpp adhesion layer [ 34 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Previous reports for the thickness of EtOHpp under the same conditions ranged from 30–40 nm [ 33 ], which is within the range what has been achieved in this work. The same applies for the HMDSOpp adhesion layer [ 34 ].…”
Section: Resultssupporting
confidence: 88%
“…For this work, three different plasma polymers were necessary. First, plasma polymerised Ethanol (EtOHpp), because it is suitable as a control sample by providing good adhesion for both and [ 33 ]. Second, plasma polymerised Hexamethyldisiloxane (HMDSOpp) was used as an adhesion layer for the TEMPOpp coatings to prevent delamination from the silicon substrate [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fantin et al suggested to work in an acidic environment to prevent end-group cyclization . Michl et al built on this by selecting SI-ARGET-ATRP and were able to graft poly­(methacrylic acid) (PMAA) brushes with a film thickness of ∼60 nm within 1 h reaction time . However, since recognition of targets in MIPs can greatly depend on the formation of H-bonds, this can be a troublesome solution.…”
Section: Introductionmentioning
confidence: 99%
“…35 Michl et al built on this by selecting SI-ARGET-ATRP and were able to graft poly(methacrylic acid) (PMAA) brushes with a film thickness of ∼60 nm within 1 h reaction time. 36 However, since recognition of targets in MIPs can greatly depend on the formation of H-bonds, this can be a troublesome solution. Haupt and co-workers reported the grafting of P(MAA-co-EGDMA) MIP films from SiO 2 nanoparticles and planar substrates using iridium-catalyzed photo-ATRP.…”
Section: Introductionmentioning
confidence: 99%